The Assessment of Hedge Effectiveness - Cristina BUNEA-BONTAS (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2012)
Earnings volatility can be a significant source of concern for a company, putting pressure on its capital base and share price. Prudent management of the company’s exposure to different risks typically involves hedging solutions. Hedging is important for corporate risk management, involving reducing the exposure of the company to specific risks. The aim of this paper is to examine the basic requirements for assessing the hedge effectiveness, this being a vital stage in applying hedge accounting, that gives the possibility to assess if the companies match the timing of the gains and losses of hedged items and their hedging derivatives. The article identifies some difficulties encountered by companies and choices that they must make in assessing hedge effectiveness.